Dynamism of Sports Marketing on Organization of Professional Football clubs in Kwara State Nigeria - Abdulraheem Mulikat (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2022)
This study investigated the dynamism of Sports Marketing in the organization of professional football clubs in Kwara State, Nigeria. The objectives of this study were to assess the relationship between advertisement, a brand of sports product, and the organization of professional football clubs. A descriptive research design of survey type was used. The population for the study comprises sports administrators in the sports council and management of Kwara United and Abubakar Bukola Saraki Football club. A multistage sampling procedure was used to select 120 respondents. The researchers-structured questionnaire was used for the study. The instrument was validated by experts in the Department of Human Kinetics Education and Marketing Department, University of Ilorin. The reliability level of the Instrument was established through the test re-test method using Pearson Product Moment Correlation (PPMC). A correlation co-efficiency of 0.87r was obtained. The administration of the instrument was done by researchers. The data collected were analyzed using Inferential Statistics of Pearson Product Moment Correlation (PPMC) at a 0.05 alpha level. The result revealed that there was a significant relationship between advertisement, branding of sports products, and organization of professional football clubs. The study recommends that there is a need for clubs management and other stakeholders at various clubs to encourage the private sector to partner with them in the area of market strategies by placing their advertisement on the club jersey.